Durability of Protection Afforded by Fewer Doses of the HPV16/18 Vaccine: The CVT Trial. (28th August 2017) - Safaeian, Mahboobeh; Sampson, Joshua N.; Pan, Yuanji; Porras, Carolina; Kemp, Troy J.; Herrero, Rolando; Quint, Wim; van Doorn, Leen Jan; Schussler, John; Lowy, Douglas R.; Schiller, John; Schiffman, Mark T.; et al.
Abstract: Background: Previously, we demonstrated similar human papillomavirus (HPV)16/18 vaccine efficacy estimates and stable HPV16/18 antibody levels four years postvaccination in a nonrandomized analysis of women who received a varying number of doses of the bivalent HPV16/18 vaccine. Here we extend data to seven years following initial vaccination. Methods: We evaluated HPV16/18-vaccinated women who received one (n = 134), two (n0/1 = 193, n0/6 = 79), or three doses (n = 2043) to a median of 6.9 years postvaccination. Cervical HPV DNA was measured with the SPF10- DEIA-LiPA PCR system; HPV16/18-specific antibody levels were measured using enzyme-linked immunosorbent assays (n = 486). Infection and immunological measures were compared across vaccine dose groups. Prevalent HPV infection at year 7 was also compared with an unvaccinated control group (UCG). All statistical tests were two-sided. Results: Among women in the three-dose, two-dose0/6, two-dose0/1, and one-dose groups, cumulative incident HPV16/18 infection rates (No. of events/No. of individuals) were 4.3% (88/2036, 95% confidence interval [CI] = 3.5% to 5.3%), 3.8% (3/78, 95% CI = 1.0% to 10.1%), 3.6% (7/192, 95% CI = 1.6% to 7.1%), and 1.5% (2/133, 95% CI = 0.3% to 4.9%; P = 1.00, .85, .17 comparing the two-dose0/6, two-dose0/1, and one-dose groups to the three-dose group, respectively). The prevalence of other carcinogenic and noncarcinogenic HPV types, excluding HPV16/18/31/33/45, were high and not statistically different among all dose groups, indicating that the low incidence of HPV16/18 in the one- and two-dose groups was not due to lack of exposure. At seven years, 100% of participants in all dose groups remained HPV16 and HPV18 seropositive. A non–statistically significant decrease in the geometric mean of the HPV16 antibody levels between years 4 and 7 was observed among women in the three-dose group: –10.8% (95% CI = –25.3% to 6.6%); two-dose (0/6 months) group: –17.3% (95% CI = –39.3% to 12.8%), two-dose (0/1 month) group: –6.9% (95% CI = –22.1% to 11.2%), and one-dose group: –5.5% (95% CI = –29.7% to 27.0%); results were similar for HPV18. Conclusions: At an average of seven years of follow-up, we observed similar low rates of HPV16/18 infections and slight, if any, decreases in HPV16/18 antibody levels by dose group.